2021
DOI: 10.1002/ejlt.202000104
|View full text |Cite
|
Sign up to set email alerts
|

Gurum Seeds: A Potential Source of Edible Oil

Abstract: Cucurbitaceae family seeds are mostly discarded as agro‐industrial wastes. Gurum (Citrullus lanatus var. colocynthoide) is an underutilized wild cucurbit plant, closely related to desert watermelon, which is grown abundantly in some African countries. Gurum seeds can play a significant role in health and nutrition due to their high oil content. This review describes the nutritional composition of gurum seeds and their oil profile. Gurum seeds are a good source of oil (27–35.5%), fiber (26–31%), crude protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…Table 1 illustrates the changes in the fatty acid profile of gurum seed oil (GSO) and microencapsulated gurum seed oil (MGSO) during 28 days of accelerated storage (60°C). Fresh GSO is rich in unsaturated fatty acids (82.13%), which is within the range of 80.2%–83.19% reported for unsaturated fatty acids of gurum seed oil extracted with different extraction methods (Karrar et al., 2021b). Linoleic acid (C18:2 ω–6, 61.96%) is the major fatty acid in GSO, followed by oleic (C18:1 ω–9, 19.23%), palmitic (C16:0, 8.90%) and stearic (C18:0, 8.86%) acids.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Table 1 illustrates the changes in the fatty acid profile of gurum seed oil (GSO) and microencapsulated gurum seed oil (MGSO) during 28 days of accelerated storage (60°C). Fresh GSO is rich in unsaturated fatty acids (82.13%), which is within the range of 80.2%–83.19% reported for unsaturated fatty acids of gurum seed oil extracted with different extraction methods (Karrar et al., 2021b). Linoleic acid (C18:2 ω–6, 61.96%) is the major fatty acid in GSO, followed by oleic (C18:1 ω–9, 19.23%), palmitic (C16:0, 8.90%) and stearic (C18:0, 8.86%) acids.…”
Section: Resultssupporting
confidence: 72%
“…Linoleic acid (C18:2 ω-6, 61.96%) is the major fatty acid in GSO, followed by oleic (C18:1 ω-9, 19.23%), palmitic (C16:0, 8.90%) and stearic (C18:0, 8.86%) acids. Similarly, previous reports indicated that linoleic acid is the major fatty acid, followed by oleic and palmitic in different seed oils (Zhang et al, 2020;Karrar et al, 2021b). Despite the high health quality of unsaturated fatty acids containing oil, such oils are unstable and rapidly oxidised during storage, which limits their utilisation in food and pharmaceutical applications (Aslan et al, 2021;Karrar et al, 2021a).…”
Section: Changes In Fatty Acids Profile During Accelerated Storagementioning
confidence: 87%